Student and Faculty Perceptions of OpenStax in High Enrollment Courses - Watson, C. Edward; Domizi, Denise; Clouser, Sherry (International Review of Research in Open and Distributed Learning, 2017)
As public funding for higher education decreases and the cost to students to attend college increases, universities are searching for strategies that save students money while also increasing their chances for success. Using free online textbooks is one such strategy, and the OpenStax College initiative at Rice University is one of the most widely recognized producers of such materials. Through a mixed method approach, this article examines the student and faculty experiences of adopting and using an OpenStax textbook. With 1,299 student participants, it was found that students greatly value the quality, attributes, and the cost of the OpenStax Biology textbook, though minor concerns were raised about its online format. Faculty adoption of a free textbook provides unique opportunities for course redesign and improvement, and the approach employed in this course transformation context resulted in clearly articulated learning outcomes, a fully realized structure in the course’s learning management system, and improvements to instructional practice. The student, faculty, and course benefits of this study offer a compelling argument for the adoption of high quality open education resources (OER) in public higher education contexts.